TRANSMISSION OF ELASTIC P-WAVES ACROSS SINGLE FRACTURES WITH A NONLINEAR NORMAL DEFORMATIONAL BEHAVIOR - Zhao J.; Cai J.G. (My University, 2001)
This paper presents a theoretical study on normally incident elastic P-wave transmission across single dry fractures with a nonlinear normal deformational behavior. The effects of nonlinear fracture normal behavior on P-wave transmission are examined without the mixture of fracture shear behavior. The linear displacement discontinuity model for wave propagation across fractures is extended to a nonlinear model - the hyperbolic elastic model (BB model). Numeric solutions of magnitudes of transmission (|Tnonand reflection (|Rnoncoefficients, for normally incident P-wave transmission across the nonlinear deformable fractures, are obtained and related to the closure behavior of fractures. Parametric studies are conducted to acquire an insight into the effects of the nonlinear fracture normal deformation on P-wave transmission, in terms of initial normal stiffness and the ratio of current maximum closure to maximum allowable closure of the fractures, as well as the incident wave amplitude and frequency. Comparisons between the linear and nonlinear models are presented. It is shown that, |Tlinnd |Rlinor the linear model are special solutions of |Tnonnd |Rnonor the nonlinear model, when the incident wave amplitude is so low that the current maximum closure of fracture incurred during the wave transmission is much smaller, relative to the maximum allowable closure. In addition, the nonlinear fracture behavior gives rise to a phenomenon of higher harmonics during the wave transmission across the fracture. The higher harmonics contribute to the increase of |Tnonrom |Tlin/P>